Efforts Of Women's And Children's Services Unit In Solving The Crime Of Sexual Abuse Committed By Minors - La Gurusi (Jurnal Hukum Volkgeist, 2023)
This research aims to look at the efforts of Women’s and Children’s Services Unit in solving the crime of suxual abuse committed by minors. This research applied empirical juridical research with the research location in the Women's and Children's Services Unit. The author in this research conducts initial data collection to obtain data or collect various data, facts and information needed. Based on the result, there was an increase in criminal cases from 2020, (4 cases) (1 case) resolved through the diversion process, in 2021 the number of cases increased to 7 cases with 2 cases resolved through diversion and restorative justice and in 2021 until December 31 the number of cases according to 5 cases and up to stage II. From the interview data obtained that children are not only victims but also perpetrators of almost all types of criminal acts. After the author conducted a deeper elaboration from the UPPA investigator of Buton Police, the fact that children become perpetrators of criminal acts is influenced by the surrounding environment, there are no examples of good character from the figures in the house and the indifference shown both in the family environment and the wider environment. Keywords: Crime, Sexual Abuse, Minors